EHS and AHS guidelines for treatment of primary ventral hernias in rare locations or special circumstances. Issue 2 (9th January 2020) - Henriksen, N A; Kaufmann, R; Simons, M P; Berrevoet, F; East, B; Fischer, J; Hope, W; Klassen, D; Lorenz, R; Renard, Y; Garcia Urena, M A; Montgomery, A
Abstract: Background: Rare locations of hernias, as well as primary ventral hernias under certain circumstances (cirrhosis, dialysis, rectus diastasis, subsequent pregnancy), might be technically challenging. The aim was to identify situations where the treatment strategy might deviate from routine management. Methods: The guideline group consisted of surgeons from the European and Americas Hernia Societies. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used in formulating the recommendations. The Scottish Intercollegiate Guidelines Network (SIGN) critical appraisal checklists were used to evaluate the quality of full-text papers. A systematic literature search was performed on 1 May 2018 and updated 1 February 2019. The Appraisal of Guidelines for Research and Evaluation (AGREE) instrument was followed. Results: Literature was limited in quantity and quality. A majority of the recommendations were graded as weak, based on low quality of evidence. In patients with cirrhosis or on dialysis, a preperitoneal mesh repair is suggested. Subsequent pregnancy is a risk factor for recurrence. Repair should be postponed until after the last pregnancy. For patients with a concomitant rectus diastasis or those with a Spigelian or lumbar hernia, no recommendation could be made for treatment strategy owing to lack of evidence. Conclusion: This is the first European and American guideline on the treatment of umbilical and epigastric hernias in patients with special conditions, including Spigelian and lumbar hernias. All recommendations were weak owing to a lack of evidence. Further studies are needed on patients with rectus diastasis, Spigelian and lumbar hernias. Graphical Abstract: This guideline addresses the treatment of umbilical and epigastric hernias in clinically challenging situations (cirrhosis, dialysis, subsequent pregnancy, rectus diastasis), as well as the treatment of Spigelian and primary lumbar hernias. Emphasises the need for better evidence